Anti-Inflammatory Potential of Punarnavadi Churna- A Polyherbal Formulation - Mahendra Vishwakarma; Manmath K. Nandi; Shruti Pandey (International Journal of Ayurveda and Pharma Research, 2025)
Punarnavadi Churna is a polyherbal Ayurvedic medicine traditionally used in the treatment of abdominal diseases (Udar roga), oedema (Shotha) and ulcer (Vran roga). This study investigates the potential use of Punarnavadi Churna in managing inflammation through its key herbal ingredients, which include Punarnava (Boerhavia diffusa), Haridra (Curcuma longa), Daruhaldi (Berberis aristata), Devdaru (Cedrus deodara), Haritaki (Terminalia chebula), and Kantakari (Solanum surratense). These herbs are known for their potent anti-inflammatory properties due to the presence of active compounds that target inflammatory pathways. The primary anti-inflammatory mechanism of Punarnavadi Churna is its ability to inhibit pro-inflammatory cytokines and reduce oxidative stress, both of which play a significant role in inflammatory conditions. For example, Punarnava (Boerhavia diffusa) is known for its diuretic and anti-inflammatory effects, which helps to reduce inflammation and fluid retention. Haridra (Curcuma longa) contains curcumin, a powerful anti-inflammatory and antioxidant potential that has been studied a lot for its ability to reduce chronic inflammation. Other herbs such as Daruhaldi (Barberis aristata) and Devdaru (Cedrus deodara) also contribute to the ability of pain and inflammation. Research, which includes animal studies and clinical observations, has verified that Punarnavadi Churna is powerful in dealing with inflammatory conditions like arthritis and edema. The synergistic potential of these herbs complements their healing advantages, making Punarnavadi Churna a promising alternative in integrative fitness practices. Its ability to address multiple pathways of inflammation makes it a valuable natural treatment, supporting overall health and wellness through holistic, plant-based remedies.